The role of ion‐transporting proteins in the evolution of salt tolerance in charophyte algae. Issue 3 (28th April 2021) - Phipps, Shaunna; Goodman, Charles A.; Delwiche, Charles F.; Bisson, Mary A.
Abstract : Species within the genus Chara have variable salinity tolerance. Their close evolutionary relationship with embryophytes makes their study crucial to understanding the evolution of salt tolerance and key evolutionary processes shared among the phyla. We examined salt‐tolerant Chara longifolia and salt‐sensitive Chara australis for mechanisms of salt tolerance and their potential role in adaptation to salt. We hypothesize that there are shared mechanisms similar to those in embryophytes, which assist in conferring salt tolerance in Chara, including a cation transporter ( HKT ), a Na + /H + antiport ( NHX ), a H + ‐ATPase ( AHA ), and a Na + ‐ATPase ( ENA ). Illumina transcriptomes were created using cultures grown in freshwater and exposed to salt stress. The presence of these candidate genes, identified by comparing with genes known from embryophytes, has been confirmed in both species of Chara, with the exception of ENA, present only in salt‐tolerant C. longifolia . These transcriptomes provide evidence for the contribution of these mechanisms to differences in salt tolerance in the two species and for the independent evolution of the Na + ‐ATPase. We also examined genes that may have played a role in important evolutionary processes, suggested by previous work on the Chara braunii genome. Among the genes examined, cellulose synthase protein ( GT43 ) and response regulator ( RRB ) were confirmed in both species. Genes absent from all three Chara species were members of the GRAS family, microtubule‐binding protein ( TANGLED1 ), and auxin synthesizers ( YUCCA, TAA ). Results from this study shed light on the evolutionary relationship between Chara and embryophytes through confirmation of shared salt tolerance mechanisms, as well as unique mechanisms that do not occur in angiosperms.